Berberine hydrochloride enhances innate immunity to protect against pathogen infection via p38 MAPK pathway - Xiao, Yi; Cui, Yingwen; Zhang, Yan; Fu, Wenqiao; Liu, Yun; Liu, Fang (Frontiers in Immunology, 2025)
The p38 MAPK pathway, an evolutionarily conserved mechanism, plays a crucial role in defending hosts against bacterial infections in both mammals and nematodes. Activating p38 MAPK signaling has been identified as a promising strategy to strengthen innate immunity and enhance resistance to pathogenic infections across various organisms.Berberine hydrochloride (BH), an isoquinoline alkaloid derived from Coptis, is known for its diverse biological activities, including anticancer, antibacterial, anti-inflammatory, lipid-lowering, and hepatoprotective effects. However, its impact on innate immunity and the associated molecular mechanisms remains unclear. In this study, we discovered that 10 μM Berberine hydrochloride enhanced resistance against both Gram-negative pathogens, such as Pseudomonas aeruginosa, Salmonella enterica and Gram-positive pathogen Listeria monocytogenes. Notably, Berberine hydrochloride improved pathogen resistance by reducing bacterial load in the intestine. Screening of classical innate immune pathways in Caenorhabditis elegans revealed that Berberine hydrochloride conferred protection against infections through the p38 MAPK pathway, specifically by activating p38/PMK-1 signaling in the intestine to bolster innate immunity. Furthermore, Berberine hydrochloride also stimulated innate immunity in mice via the p38 MAPK pathway and significantly reduced bacterial load in the lungs. These findings indicate that Berberine hydrochloride may have therapeutic potential for protecting host from infectious diseases.